Posyandu Service Innovation in the Pandemic Time Covid-19 with the Door to Door Method to the Attitudes of Parents and the Growth, Development of Toddler in the Working Area of the Sukorame Puskesmas, Kota Kediri - Reny Maswiyati; Yuly Peristiowati (Journal for Quality in Public Health, 2022)
Posyandu is a form of Community Based Health Efforts (UKBM) which is managed from, by, for, and with the community, in order to empower the community and provide convenience to the community in obtaining basic health services. The Covid-19 virus outbreak affects Posyandu activities. However, during the Covid-19 pandemic, activities at the posyandu must still be carried out, because monitoring the growth and development of toddlers must not stop. The purpose of this study was to determine the difference between the posyandu service innovations during the Covid-19 pandemic between the door to door method posyandu and conventional posyandu on the attitudes of parents and the growth and development of toddlers in the working area of ​​the Sukorame Public Health Center, Kediri City. This research is an experimental research. The sample in this study consisted of 50 parents who had toddlers for the door to door posyandu method and 50 parents who had toddlers for conventional posyandu who carried out posyandu activities in June 2021. Data were obtained from questionnaires, KMS and DDTK. Data analysis using T-test. T-test results show Sig(2-tailed) > 0.05 so that it can be concluded that there is no significant difference between parental attitudes, growth of toddlers and development of toddlers between posyandu with door to door method and conventional posyandu.